2P-Lookup: Popularity and Proximity based P2P Lookup mechanism over MANETs. (August 2016) - Seddiki, Manel; Benchaïba, Mahfoud
Abstract: With the emergence of P2P applications and mobile devices, users express the need of exchanging data anywhere, anytime. This encouraged the deployment of P2P applications on mobile environment. In resource sharing applications over mobile ad hoc networks, resource search mechanisms reveal new challenges because of the mismatch between the P2P overlay and the MANET underlay and the critical constraints of MANET nodes (high mobility and energy limitation). In this paper, we propose 2P-Lookup, a Popularity and Proximity based P2P Lookup mechanism over MANETs. Our mechanism is composed of two main steps: in the first one, we propose a cross-layer optimization which consists in building the P2P overlay based on physical proximity of peers in order to reduce the mismatch between the overlay and the MANET topologies. This optimization likely matches between overlay and underlay paths which consequently reduces the search delay, increases the success rate, reduces communication redundancy and unnecessary network traffic. In the second step, we focus on the search query routing and we propose a resource popularity-biased random walk to efficiently guide the search query and control its propagation. Our biased random walk optimization further reduces the network traffic without influencing the search success rate. Simulation results show that 2P-Lookup is efficient in a MANET underlay and have better search performances comparing to other related works. Abstract : Highlights: We propose 2P-Lookup, a Popularity and Proximity based P2P resource Lookup over MANETs. The strength of 2P-Lookup is the exploitation of: (1) Mobile nodes proximity to build overlay links in order to reduce overlay paths and remove communication redundancy in the network, (2) The resource popularity to guide the search query in order to increase search success rate and decrease the delay. In the beginning of the manuscript, we present a detailed background and state of the art of the existing resource search techniques over MANETs. Next, we detail 2P-Lookup design and finally we evaluate its performances. Simulation results consolidate our design and show that being aware of the MANET underlay and exploiting the resource popularity offer promising search performances in a mobile P2P environment.